A Characterization of Alcohol Use In Active Military Personnel at Fort Riley, KS - Dysart, Valerie (My University, 2012)
My Capstone Field Experience was spent with the Fort Riley Public Health Department in Fort Riley, KS. The experience consisted of two parts. The first included observing and working with the various areas within the Public Health Department in order to develop an understanding of the range of specialties involved in public health services. Secondly, I conducted a research project to characterize the use of alcoholic beverages by active duty personnel at Ft. Riley. I describe the current trends in use of alcohol by military personnel, discuss negative outcomes involved with excessive drinking, and explore current as well as possible new mitigation strategies to reduce its negative impact.
Keywords: Fort Riley; Excessive drinking; Binge drinking; Active duty personnel; Public Health (0573)